Digitalisation of Malaysian agricultural sector / Baderisang Mohamed, Mohd. Sukor Md. Yusoff and Megat Daniel Arif - Mohamed, Baderisang; Md. Yusoff, Mohd. Sukor; Arif, Megat Daniel (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
The expansion of agriculture is without a doubt the most significant period in modern human history. Agriculture is the science behind farming, which entails cultivating plots of land to grow crops for human consumption (Cambridge Dictionary, 2020). Agriculture played a key role in the evolution of a more sedentary or static human civilization. The term "Neolithic Revolution" was coined in the 1920's by V. Gordon Childe, an Australian archaeologist and one of the twentieth century's foremost prehistorians (Balter, 2005). Agriculture, he asserted, was a watershed moment in the revolution because it gave early human colonies control over their own food supplies. He also asserted that, following the end of the last ice age over eleven thousand years ago, a warmer and less harsh climate compelled early humans and the few domesticated animals to migrate and congregate near fully developed rivers, oases, and other water sources. These activities laid the groundwork for most agricultural societies and early kingdoms, which grew to become great civilisations.